Relationships between amylopectin internal molecular structure and physicochemical properties of starch - Zhu, Fan (Trends in food science & technology, 2018)
Structure-property relationships of starch components remain a subject of research interest. In recent years, there has been increasing evidence revealing the importance of amylopectin internal structure in determining physicochemical properties of starch. The part between the sole reducing end and out branches of amylopectin forms the internal part of the molecule. It contributes to the formation of the amorphous lamellae of the granules. This mini-review focuses on the impact of amylopectin internal molecular structure on different physicochemical properties of starch. The properties include gelatinization, swelling power, amylose leaching, pasting, retrogradation, and digestibility of starch. The statistical approach to analyze the structure-property relationships of starch is also discussed. Related nomenclatures are described. Amylopectin with a longer internal chain length tends to give more ordered packing of double helices in the granules with a higher thermal stability. A longer internal chain length of amylopectin also contributes to the formation of recrystallized amylopectin with a more ordered structure and higher thermal stability. The results summarised in this mini-review clearly show that the molecular structure of amylopectin internal part should be considered in order to better understand the complex structure-property relationships of starch components. •Longer amylopectin internal chain related to more ordered packing of double helices.•Longer amylopectin internal chain related to more efficient recrystallization.•Importance of amylopectin internal chain composition on starch properties discussed.•Related amylopectin nomenclatures described.